The Effects of Homeownership on Wealth Distribution - Klára ČERMÁKOVÁ; Eduard HROMADA; Eduardo Aguiar Henrique FILHO; Tomáš KRULICKÝ (European Journal of Interdisciplinary Studies, 2022)
Within the broader context of new dimensions of poverty such as housing poverty, energy poverty, etc., this article describes dependencies between household income, real estate ownership and socio-economic trends. We argue that income is not the principal determinant for home ownership rate, but rather recent lifestyle changes can better explain the homeownership decreasing trend in developed economies. Job mobility, family formation determinants and demographical trends seem to find well-supported basis in literature and data. Using data for the US states we have proved that the decreasing rate of home ownership may be explained by social aspects of changing lifestyle such as increasing share of population moving from rural areas to cities, age of marriage, divorce rate, career-oriented lifestyle, rather than by the frequently cited price-income ratio. We have also observed a short-term correlation between financing availability and homeownership rate, but we conclude that property prices would adjust to lose monetary policy without any long-term effect on homeownership rate. It results that government or monetary policies aimed to cushion the housing unavailability (recently increasing value of price-income) ratio may distort the housing market. We propose a new insight in the housing availability discussion.